Analiza zdravstvenega stanja pilotov, usmerjena v telesno aktivnost kot dejavnik preprečevanja tveganja za bolezni srca in ožilja - Bilban, Marjan (Zdravstveno varstvo, 2005)
Aim: To determine health status of the Slovene air carrier's pilots, mostly interms of health-related lifestyles, and to propose appropriate physical activity to improve their health. Methods: The study conducted in 2002 included 67 pilots. Before undergoing preventive medical examinations, they were asked to complete an unstandardized questionnaire on health-related lifestyles. The acquired data were statistically processed using standard statistical methods. Results: The majority of respondents denied smoking or consuming alcohol, and reported participation in at least minimal physical activity; 64.2 per cent were physically active three or more than three times weekly, and the remainder only once weekly. Two/thirds said they had three to five meals per day. On average, the participants were slightly overnourished with total cholesterol levels slightly above normal, decreased atherogenic index and nearly ideal maximal aerobic capacity tested under strain. Favourable effects of physical activity on all risk factors for ischemic heartdisease were established. Conclusion: The results obtained will provide important information needed for planning the scope and structure of preventive medical examinations, and for developing health promotion activities with special emphasis on increasing physical activity and dicouraging bad habits and inappropriate eating practices.
Keywords: cardiovascular disease; dejavniki tveganja; kardiovaskularne bolezni; piloti; telesna aktivnost; zdravstveno stanje